Selective binding of tumor suppressor p53 protein to topologically constrained DNA: modulation by intercalative drugs - Pivoňková, Hana; Šebest, Peter; Pečinka, Petr; Tichá, Olga; Němcová, Kateřina; Brázdová, Marie; Brázdová Jagelská, Eva; Brázda, Václav; Fojta, Miroslav (Biochemical and biophysical research communications, 2010)
Selective binding of the wild type tumor suppressor protein p53 to negatively and positively supercoiled (sc) DNA was studied using intercalative drugs chloroquine (CQ), ethidium bromide, acridine derivatives and doxorubicin as a modulators of the level of DNA supercoiling. The p53 was found to lose gradually its preferential binding to negatively scDNA with increasing concentrations of intercalators until the DNA negative superhelix turns were relaxed. Formation of positive superhelices (due to further increasing intercalator concentrations) rendered the circular duplex DNA to be preferentially bound by the p53 again. CQ at concentrations modulating the closed circular DNA topology did not prevent the p53 from recognizing a specific target sequence within topologically unconstrained linear DNA. Experiments with DNA topoisomer distributions differing in their superhelix densities revealed the p53 to bind selectively DNA molecules possessing higher number of negative or positive superturns. Possible modes of the p53 binding to the negatively or positively supercoiled DNA and tentative biological consequences are discussed.
Keywords: interkalátory; DNA, Superhelical; Doxorubicin; konformace nukleové kyseliny; Binding, Competitive; Tumor Suppressor Protein p53; Acridines; lidé; superhelikální DNA; chlorochin; Intercalating Agents; nádorový supresorový protein p53; kompetitivní vazba; Nucleic Acid Conformation; akridiny; Chloroquine; doxorubicin; Humans